Correlation Between Air Quality Index and Tear Film Lipid Layer Thickness: Comparison Between Patients with Sjogren's Syndrome and with Meibomian Gland Dysfunction. (4th May 2023) - Wang, He; Jia, Hui; Han, Jiaxin; Zhang, Zhaowei; Yin, Xiaoyue; Mu, Ning; Zhu, Yanan; Li, Mingxin
Abstract: Purpose: To evaluate the effect of air pollution on the tear film stability by analyzing the correlation between Air Quality Index (AQI) and Lipid Layer thickness (LLT) in Xuzhou. Methods: As a prospective descriptive observational study, 284 patients with meibomian gland dysfunction (MGD), 157 patients with Sjögren's syndrome (SS), and 264 healthy volunteers were included. The tear film lipid layer thickness of the three groups of subjects was measured weekly and compared with the air quality index to analyze the correlation between the two indicators. Logistic regression analysis and linear regression analysis were used to analyze the effect of AQI on the thickness of the tear film lipid layer. The change of LLT with air pollution at different AQI levels was also analyzed. Results: There are obvious seasonal differences in the changes of air pollution index in Xuzhou. Significant differences could be observed in the thickness of the lipid layer of the tear film among the three groups. LLT in the MGD group and SS group decreased with the aggravation of air pollution, while remained unchanged in the control group. There was strong evidence of correlation between LLT of the MGD group ( F = 353.494, p < 0.01, adjusted R2 = 0.695) and the SS group ( F = 502.404, p < 0.01, adjusted R2 = 0.764) with AQI, while there was minor correlation between LLT with AQI in control group ( F = 8.525, p < 0.01, adjusted R2 = 0.046). Conclusions: Air pollution can cause a decrease in the thickness of the tear film lipid layer, thereby affecting tear film stability, leading to the occurrence of dry eye.